Field study and reactive simulation of iron migration in groundwater during the riverbank filtration. (January 2021) - Kazak, Ekaterina S.; Pozdniakov, Sergey P.
Abstract: Water supply in Voronezh city, Russian Federation with the population more than 1, 1 million people are based only on the groundwater of alluvial the Neogene-Quaternary (N-Q). Due to the riverbank filtration (RBF), the contaminated groundwater provinces with iron pollution formed in the alluvial aquifer. The high iron content in groundwater interferes its use for the Voronezh city's water supply. It may even bring about the inevitable water intakes abandonment due to problems with well clogging. We performed the series of field experiments (chemical tests of groundwater, spring, rain, reservoir and pore water, aquifer and bottom sediments) and numerical simulation to detect the potential iron source in pumped groundwater by riverbank water wells. We found that during the RBF, two contrary processes of Fe behaviour take place. On the one hand, the iron accumulation and transformation due to the iron hydroxides reduction by dissolved organic matter, occur in the bottom sediment. On the other hand, we observe the iron removal process from the bottom sediment due to Fe migration with attracted surface water along hydraulic pathways "surface water – bottom sediments – aquifer – pumping wells". Finally, the mix of the attracted water with dissolved iron with natural Fe-free groundwater coming from the watershed forms the iron concentration pattern in pumping groundwater. The simulation results show that in the 3rd year of the RBF, the iron content reaches a maximum value in pumping groundwater and does not change for the operation time (25 years). Moreover, we have shown that during the long RBF, the iron pollution area will extend and even the northern and southern aquifer parts of the water intake facility will be contaminated by iron. Graphical abstract: Image 1 Highlights: The research of the Fe pollution of pumped groundwater includes field and laboratory investigations and numerical modelling. High dissolved Fe 2+ concentration of the reductive pore water depends on the fulvic acid content. Fe-minerals of the Voronezh Reservoir bottom sediment are the main source of iron pollution in pumping groundwater.